Pendampingan Pemahaman Materi Sejarah Kebudayaan Islam Siswa Kelas XI MA Ma’arif Klego Ponorogo - Amri, Ulil; Fikri, M. khairul; Diansyah, Nur; Sidik, Fajar; Malikah, Nurul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to explore the impact of mentoring on improving the understanding of Islamic cultural history among 11th-grade students at MA Ma'arif Klego. The research method used is qualitative, and data were collected through interviews with 11th-grade students regarding the Islamic Cultural History (SKI) learning process. The results of the study indicate that mentoring significantly enhances the understanding of Islamic cultural history among the 11th-grade students at MA Ma'arif Klego. The mentoring group showed higher understanding scores than the non-mentoring group. Additionally, observations of the learning process indicated more active participation and better understanding from students who received mentoring. These findings have important implications for teaching practices in schools, especially in the context of understanding Islamic cultural history. Mentoring can be an effective strategy in helping students grasp complex concepts and strengthen their learning in the classroom. Future research could develop more specific mentoring approaches and evaluate their long-term impact.